Style and Idea: Selected Writings - Schoenberg, Arnold 1874-1951; Stein, Leonard; Black, Leo (London Faber and Faber, 1984)
One of the most influential collections of music ever published, Style and Idea includes Schoenberg's writings about himself and his music as well as studies of many other composers and reflections on art and society.
Keywords: Composing; Music criticism